Dearth of Distinct Exam Centres in Bangladesh: Teaching and learning Disruptions for Closures during Public Examinations - Qader, Md. Abdul (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2022)
In the setting of education, examinations are generally well-thought-out of the method of assessment. These are not only the powerful ways of improving learning but also assessing whatever learners have learned. But when these examinations are disturbing to teaching and learning, what circumstance will be emerged in this educational setting? In Bangladesh, some schools and colleges are governmentally selected as the centres of various public examinations. During these examinations, teaching and learning activities of those educational institutions were closed down for imposing section 144 in 400 yards around the centres. For this reason, it is difficult to complete the syllabus of all subjects and the teaching and learning process of those institutions are hampered. The manuscript intended to focus on the degree of level of the problem created by interrupted teaching and learning of those center schools and colleges during public examinations in Bangladesh. It also aimed at finding out the actual solution of the problem. The research was conducted in mixed method prioritizing quantitative method. Three instruments of data collection were used: Questionnaire-survey among 157 participants concerned in teaching and learning directly and indirectly, Focus Group Discussion (FGD) among 8 educational administrators, and Content Analysis (CA) of existing knowledge or remaining relevant data from various local newspapers: daily star, daily observer, daily Prothom Alo, etc. The manuscript also recommend a solution that government should construct distinct exam-complex (multi-storied building) in each sub-district in the countries like Bangladesh. Finally, the research work is significant for examination management of Bangladesh and that of other countries like Bangladesh.